Insights into Commune Council Leadership: Case of Decentralization Reform in Choueng Prey District, Cambodia - Han, Kosal; Yen, Yat (Brawijaya University, 2024)
Decentralization reform has been adopted by the Cambodian government since 2001, bringing the government and services closest to the people through the commune council, the lowest tier of subnational administration. The reform has contested local leadership to the premise of decentralization and local democracy based on good governance. To look into such a contest of a two-decade-long decentralization reform, this research aims to examine in-depth insights into the leadership capacity of the commune council in Cambodia upon the case of Choueng Prey district, Kampong Cham province. With the adoption of qualitative methodology along with score-based assessments, the results of this research uncovered the perspectives on local leadership. The results suggested that the current decentralization reforms need further reforms with stronger and more genuine political commitment of the government in return for local sustainable development and effective public service delivery. Evidentially, the leadership of the commune council has been identified to be relatively deficient due to the durable existence of a low education standard for the council candidates, the meagre structure of commune council management, and the privation of procedures for selecting and recruiting the council candidates. These are key focuses to results and discussion because they are believed to be fundamental drivers in shaping the quality of commune council leadership which is a cornerstone of this research.